Pyrazole Schiff Base Hybrids as Anti-Malarial Agents: Synthesis, In Vitro Screening and Computational Study - Aggarwal, Shilpy; Paliwal, Deepika; Kaushik, Dhirender; Gupta, Girish K.; Kumar, Ajay (Combinatorial Chemistry & High Throughput Screening, 2018)
Background: Malaria is one of the most vital infectious diseases caused by protozoan parasites of the Plasmodium genus. As P. falciparum, the cause of most of the severe cases of malaria, is increasingly resistant to available drugs such as amodioquine, chloroquine, artemisinin, and antifolates, there is an urgent need to identify new targets for chemotherapy. Objective: This study screened novel pyrazole derivatives carrying iminium & benzothiazole group for antimalarial potential against P. falciparum chloroquine sensitive (3D7) strain. Materials & Methods: Several pyrazole schiff base hybrids with a wide range of substitution have been synthesized via condensation of substituted aniline with substituted 4-formylpyrazole and evaluated for their in vitro antimalarial activity against asexual blood stages of human malaria parasite, Plasmodium falciparum. The interaction of these conjugate hybrids was also investigated by molecular docking studies in the binding site of P. falciparum cystein protease falcipain-2. The pharmacokinetic properties were also studied using ADME prediction. Results: Among all compounds, 6bf and 6bd were found to be potential molecules with EC50 1.95μg/ml and 1.98μg/ml respectively. Docking study results reveal that the pyrazole schiff base derivatives occupy the PfFP binding sites and they show good interactions with significant values of binding energies. Conclusion: We provide evidence which implicates pyrazole Schiff base hybrids as potential prototypes for the development of antimalarial agents.
Keywords: Pyrazole